Spontaneous Uterine Perforation of Pyometra Presenting as Acute Abdomen - Toshihiro Kitai; Kentaro Okuno; Hiromi Ugaki; Yoshiko Komoto; Satoshi Fujimi; Masahiko Takemura (Hindawi Limited, 2014)
Pyometra is the accumulation of pus in the uterine cavity, and spontaneous perforation of pyometra resulting in generalized diffuse peritonitis is extremely uncommon. We report a rare case of diffuse peritonitis caused by spontaneous perforation of pyometra. A 66-year-old postmenopausal woman with diffuse abdominal pain and vomiting was admitted to our institution. She had a history of mixed connective-tissue disease and had been taking steroids for 20 years. Under a diagnosis of generalized peritonitis secondary to perforation of the gastrointestinal tract or uterus, supravaginal hysterectomy and bilateral salpingo-oophorectomy were performed. Unfortunately, wound dehiscence and infection occurred during the postoperative course, which were exacerbated by her immunocompromised state. Despite intensive care and a course of antibiotics, the patient died of multiple organ failure resulting from sepsis on the 36th postoperative day. Although correct diagnosis, early intervention, and proper treatment can reduce morbidity and mortality of spontaneous perforation of pyometra, if severe infection occurs, this disease can be life threatening for immunocompromised hosts.